Optimizing cleft care during COVID pandemic - Devi Prasad Mohapatra; M T Friji; S Dinesh Kumar; Ravi Kumar Chittoria; Imran Pathan; K Shijina (Wolters Kluwer Medknow Publications, 2021)
The COVID-19 pandemic has created disruptions worldwide with unprecedented interruption of non-COVID health care. Cleft care services toward children with cleft lip and palate have also been affected worldwide leading to stress among cleft caregivers. The use of remote consultation and therapy finds a definitive application in such situations. We present our method of providing uninterrupted cleft care through remote consultations service during this pandemic.